Multisensory Approach in Commercial Public Space Design in East Java, Indonesia - Nisa, A K; D Nurgandarum; D Rosnarti (Talenta Publisher, 2025)
Social interaction is an activity that can never be separated from human life. Public space is community place for social activities to occur. Along with its development, public space has transformed its function into a commercial area. Commercial activities require humans to continue to be active in an environment, including in public spaces. Public space is actually a space that can be accessed by anyone, and can provide a memorable space experience for its users, from all races, social statuses, to sensory capabilities (normal and people with disabilities). But unfortunately, commercial public spaces tend to only pay attention to visual experiences and ignore other sensory experiences in human senses. This study discusses the design criteria for commercial public spaces with a multisensory approach that uses literature review methods and case studies at the Pasar Induk Kota Batu, East Java, Indonesia. This study shows that Pasar Induk Batu has met several sensory experiences which are olfactory experiences, visual experiences, haptic experiences, and auditory experiences.